POTENSI KECURANGAN (FRAUD) DALAM KLAIM PENGGANTIAN BIAYA PELAYANAN PASIEN COVID-19 - Made Subianta Adnyana; Harti Budi (Faculty of Economics and Business, Universitas Warmadewa, 2023)
The purpose of this research is to find out the potential for fraud that can occur in the process of claiming reimbursement for COVID-19 patient services. This research is a case study qualitative research through in-depth interviews with informants who are experienced auditors in examining the claims process. All informants who have been interviewed stated that the potential for fraud can occur at all stages in the claim process starting from patient service at the hospital, filing a claim by the hospital, verification by BPJS Kesehatan, and payment by the Ministry of Health. The potential for fraud stated by all informants (100%) occurred at the claim submission stage, where the hospital management filed a claim for a COVID-19 patient with a length of stay exceeding what actually happened and submitted a patient who did not meet the criteria for a COVID-19 patient.